Rule of Prevention: a potential framework to evaluate preventive interventions for rare diseases - Eddie Gibson; Daniel A. Ollendorf; Steven Simoens; David E Bloom; Federico Martinón-Torres; David Salisbury; Johan Louis Severens; Mondher Toumi; Daniel Molnar; Kinga Meszaros; Woo-Yun Sohn; Najida Begum (Journal of Market Access & Health Policy)
ABSTRACTBackground: The benefits of preventive interventions lack comprehensive evaluation in standard health technology assessments (HTA), particularly for rare and transmissible diseases.Objective: To identify possible considerations for future HTA using analogies between the treatment and prevention of rare diseases.Study design: An Expert panel meeting assessed whether one HTA assessment framework can be applied to assess both rare disease treatments and preventive interventions. Experts also evaluated the range of value elements currently included in HTAs and their applicability to rare, transmissible, and/or preventable diseases.Results: A broad range of value should be considered when assessing rare, transmissible disease prevention. Although standard HTA can be applied to transmissible diseases, the risk of local outbreaks and the need for large-scale prevention programs suggest a modified assessment framework, capable of incorporating prevention-specific value elements in HTAs. A ‘Rule of Prevention’ framework was proposed to allow broader value considerations anchored to severity, equity, and prevention benefits in decision-making for preventive interventions for rare transmissible diseases.Conclusion: The proposed prevention framework introduces an explicit initial approach to consistently assess rare transmissible diseases, and to incorporate the broader value of preventive interventions compared with treatment.